Knowledge and Attitude for Sterile Women Regarding Infertility in Thi-Qar Fertility Centers (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective of Study: To explore knowledge and attitudes about Infertility for sterile women.Methodology: A descriptive cross-sectional study of (100) sterile women selected randomly who visited inthi-Qar fertility center for the period from 3rd October 2019 to 15th January 2020. Validity and reliabilityof questionnaire are determined through pilot study. Used descriptive statistical procedures deductive dataanalysis, and data was collected from couples through predesigned interview questionnaire and attitudescale, data was analyzed by SPSS version (20). Descriptive and inferential statistic was used.Results: The result showed in the age series (25-30 years) was for the elevated proportion from the pattern.General knowledge of sterile women was (44.34 per cent), knowledge of sterile women’s risk factors was(30%). The sterile women’s attitude to infertility was negative (28.6 percent).Women’s strategies in this studywere weak (26.3 percent).Women’s age and duration of infertility were significantly correlated (PV=0.01).Recommendation: Promote education programs to raise knowledge rates and improve infertility behaviors,and promote improving infertility coping strategies.
Keywords: Knowledge, attitude, Sterile Women, Infertility.